Pajareando en el noroccidente de la provincia del Carchi, canto y encanto de las aves - Chiriboga Chamorro, Gerardo Jeovanny (Tierra Infinita, 2018)
For the characteristics of their territory that make it a country megadiverso, the Ecuador has one of the biggest concentrations in birds of the world: 1630 species that it represents 18% of birds of the planet. Ecuador is this way the country of the birds, and although he/she has its challenges environmental matters, the resource avifaunístico stays in general, enviable. The County of the Carchi embraces a surface of 3.783 Km2, it presents an irregular orography, what has generated a great variety of floors zoogeográficos, climates and ecosystems. In particular in the Noroccidente of the Carchi he/she has been carried out counts in a circular area of 24 Km, in which the information has been systematized with the collaboration of the ecological clubs and the commission of validation of registrations, the number of species and observed individuals and listened. The result was of 318 species of opposing birds. In this context, the parishes of Tufiño, Maldonado and Chical, belonging to the Cantón Tulcán, is those that bigger biodiversity of birds presents and it transforms it into a very rich area of this biological group. This investigation is an invitation to discover this whole fascinating song world and charm of the birds, which can be opposing along the whole territory of the parishes.